2015
DOI: 10.1016/j.jnutbio.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of folic acid on global DNA methylation and colonosphere formation in colon cancer cell lines

Abstract: Folate and its synthetic form, folic acid (FA), are essential vitamins for the regeneration of S-adenosyl methionine molecules, thereby maintaining adequate cellular methylation. The deregulation of DNA methylation is a contributing factor to carcinogenesis, as alterations in genetic methylation may contribute to stem cell reprogramming and dedifferentiation processes that lead to a cancer stem cell (CSC) phenotype. Here, we investigate the potential effects of FA exposure on DNA methylation and colonosphere f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 62 publications
1
35
0
1
Order By: Relevance
“…In addition, there is evidence that nutritional stimuli can modify epigenetic mechanisms, such as DNA methylation. 9 DNA methylation/demethylation plays a crucial role in gene regulation and could also be responsible for the presentation of senescence. For example, being fed a chronic HF diet mice (from weaning to >15 weeks of age) altered the patterns of DNA methylation in the brain, 10 and the OS and inflammation that increase by HF diet are thought to be important contributors of DNA hypermethylation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence that nutritional stimuli can modify epigenetic mechanisms, such as DNA methylation. 9 DNA methylation/demethylation plays a crucial role in gene regulation and could also be responsible for the presentation of senescence. For example, being fed a chronic HF diet mice (from weaning to >15 weeks of age) altered the patterns of DNA methylation in the brain, 10 and the OS and inflammation that increase by HF diet are thought to be important contributors of DNA hypermethylation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary intake and blood level of folate appear to be negatively correlated to the risk of tumorigenesis in several organs, such as the breast, colon, and lung (10)(11)(12). Recently, a number of studies have reported that high folate supplementation might cause epigenetic changes that may promote carcinogenesis (13)(14)(15)(16)(17). However, little was done about the antimutagenic effects of folate supplementation.…”
mentioning
confidence: 99%
“…In vitro studies on colon cancer cell lines showed that folic acid supplementation in medium is capable of changing DNA methylation patterns, as well as altering the proliferative capacity and phenotype of these cells in culture. This is of particular importance in understanding the role of folic acid supplementation on the behaviour of tumours in terms of phenotypic changes, motility and invasion [144]. Other studies have reported an increased proliferation due to altered DNA methylation in response to excessive folic acid supplementation [6, 145].…”
Section: Folates and Cancermentioning
confidence: 99%